Hubungan Kecerdasan Emosional Dengan Perilaku Cyberbullying Siswa di SMPN 16 Padang - Ilfa Sukma Weni; Yeni Karneli (Consilium, 2022)
The advent of technology and the internet has brought new challenges to the realm of human behavior. One such challenge is the emergence of cyberbullying, a form of bullying that occurs online. Cyberbullying has become a common problem, especially among students who spend a lot of time on social media platforms. Unlimited internet access is used by teenagers to commit crimes. One of the important roles in controlling cyberbullying behavior is emotional intelligence. Good student emotional maturity will reduce cyberbullying behavior. This study aims to (1) describe students' cyberbullying behavior (2) describe students' emotional intelligence and (3) describe the relationship between emotional intelligence and student cyberbullying. Cyberbullying behavior is influenced by factors influenced by unstable emotions carried out by students when using social media facilities. The research was conducted at SMP N 16 Padang. This research uses descriptive and correlational methods. Based on the findings, students have self-disclosure in the high category, so it is hoped that student self-disclosure can be increased to a very high level. social interaction is quite good, for it is expected that students' self-confidence can be increased to a very high level. There is a significant relationship between students' self-disclosure with students' social interactions. This means that the higher the student's self-disclosure, the higher the social interaction of students. Using the Pearson Product Moment correlation analysis technique, it can be seen that there is a significant negative relationship between emotional intelligence and cyberbullying behavior of 0.304 with a significance level of 0.041. This it means that the higher the student's emotional intelligence, the lower the cyberbullying behavior, and vice versa, the lower the emotional intelligence, the higher the student's cyberbullying behavior. The strength of the relationship between the two variables is weak because the correlation coefficient values are in the range of 0.20-0.39.Keywords: Emotional Intelligence, Cyberbullying.